Experimental Study of the Rock Mechanism under Coupled High Temperatures and Dynamic Loads - Huaming An; Tongshuai Zeng; Zhihua Zhang; Lei Liu (Advances in Civil Engineering)
With the development of modern society, geomaterials are widely used for infrastructure. These materials often experience dynamic loading and high temperature, which significantly influences the mechanical behaviour of the materials. This research focuses on the effects of the loading rate and high temperature on rock mass in terms of rock mechanism. A state-of-the-art review of rock mechanism under coupled dynamic loads and high temperatures is conducted first. The rock mechanism under static and dynamic loads is introduced. The marble is taken as the rock material for the test, while the split-Hopkinson pressure bar system is used to take the dynamic tests. In addition, the principles of the split-Hopkinson pressure bar are introduced to obtain the dynamic parameters. The fracture patterns of the uniaxial compressive strength test and the Brazilian tensile strength test are obtained and compared with those well documented in the literature. Some curves for the relationships among the loading rate, strain, temperature, compressive or tensile strengths are explained. It is conduced that with the increase of the loading rate, the rock strength increases, while with the increase of the temperature, the rock strength decreases.